A rare case of multiple paragangliomas in the head and neck, retroperitoneum and duodenum: A case report and review of the literature - Kawanabe, Shin; Katabami, Takuyuki; Oshima, Ryuichi; Yanagisawa, Nobuyuki; Sone, Masakatsu; Kimura, Noriko (Frontiers in Endocrinology, 2023)
Pheochromocytomas and paragangliomas (PGLs) are rare non-epithelial neuroendocrine neoplasms of the adrenal medulla and extra-adrenal paraganglia. Duodenal PGL is quite rare and there are only two previous reports. Herein, we report a case of multiple catecholamines (CAs)-producing PGLs in the middle ear, retroperitoneum, and duodenum, and review the literature of duodenal PGLs. A 40-year-old man complained right-ear hearing loss, and an intracranial tumor was suspected. Magnetic resonance imaging of the head revealed a 3-cm mass at the right transvenous foramen, which was surgically resected following preoperative embolization. The pathological diagnosis was a sympathetic PGL of the right middle ear. Six years later, family history of PGL with germline mutation of succinate dehydrogenase complex iron sulfur subunit B (SDHB) (NM_003000.2: c.268C>C/T, p.[Arg90Ter/Arg]) was clarified. The patient had elevated levels of plasma and urine CAs again. Abdominal computed tomography scanning revealed two retroperitoneal tumors measuring 30-mm at the anterior left renal vein and 13-mm at near the ligament of Treitz. The larger tumor was laparoscopically resected, but the smaller tumor was not identified by laparoscopy. After the operation, the patient remained hypertension, and additional imaging tests suggested a tumor localized in the duodenum. The surgically resected tumor was confirmed to be a duodenal PGL. After that, the patient remained hypertension free, and urinary levels of noradrenaline and normetanephrine decreased to normal values. No recurrence or metastasis has been found at 1 year after the second operation. CAs secretion from PGLs in unexpected location, like the duodenum of our patient, may be overlooked and leads to a hypertensive crisis. In such cases, comprehensive evaluation including genetic testing, fluorodeoxyglucose-positron emission tomography scanning, and measurement of CAs will be useful for detecting PGLs. Most previous reports on duodenal PGL were gangliocytic PGL which has been renamed composite gangliocytoma/neuroma and neuroendocrine tumor, and defined the different tumor from duodenal PGL. We reviewed and discussed duodenal PGLs in addition to multiple PGLs associated with SDHB mutation.